THE QUESTION OF HUMANITARIAN KNOWLEDGE: THE ESSENCE, MAIN DIRECTIONS AND METHODS - Anatoly V. Zavrazhin (Статистика и экономика, 2016)
In the article the author emphasizes the role and importance of humanitarian knowledge not only in education, training future professionals, but in an objective, true evaluation of the events which occur today in the modern world. Reveals the methodological foundations, purpose, main directions and methods of humanitarian knowledge. Highlighted the special role in the Humanities.